Results of integration of Ukrainian education into the European educational area (Educational Dimension, 2021)
The article examines issues related to the integration of the educational system of Ukraine into the European educational area. Based on the analysis of the legal framework of the European institutions regulating issues in education and the humanitarian sphere, the chronology of the creation of a common European educational area from the Bologna Declaration to the present is generalized. The key decisions and their achievements are determined, the peculiarities of the course of integration processes in EU education are traced. It was found that the indicators of the success of the implementation of decisions in the field of education are primarily numerical indicators that set the boundaries of both positive and negative phenomena in education. On the basis of normative documents, analytical articles and other documents adopted in Ukraine, an attempt is made to summarize information on measures implemented in Ukraine aimed at European integration in education, and to identify those challenges that need to be addressed in the context of new socio-political, economic and humanitarian challenges. Tasks facing education in the sphere of integration are: coordination with European countries of key indicators that characterize the level of education; determination of quantitative parameters of education quality, achievement of which is necessary; optimization of management models and investments in education, including by foreign investors, business structures at both the state and regional levels, taking into account decentralization; transformation of the content of education from the standpoint of the competence approach; development of valid methods of assessment of subject competencies; bringing education closer to both social needs and the needs of the labor market.